2019
DOI: 10.17523/bia.2019.v76.e1449
|View full text |Cite
|
Sign up to set email alerts
|

Blood parameter of Nellore steers submitted to different levels of feed intake

Abstract: Blood parameters of 18 Nellore steers submitted to high concentrate diet in two sequential feeding regimes (phase 1: restriction and phase 2: ad libitum feeding) were evaluated. In the first phase, steers were fed for 56 days three intake levels of dry matter (ad libitum, 75 g dry matter (DM)/kg metabolic body weight (BW 0.75) or 60 g DM/kg BW 0.75. In the second phase, from the 57 th day on feed, animals fed 60 g DM/kg BW 0.75 and 75 g DM/kg BW 0.75 were fed ad libitum until the 136 th day. In the 8 th , 27 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
0
0
1
Order By: Relevance
“…However, when fed a high-concentrate diet, values can exceed 70 mg dL −1 . For example, Aferri et al (2019) found 129.23 mg dL −1 of blood glucose in Nellore cattle confined with 800 g kg DM −1 of concentrate in the diet. Furthermore, glycemia in cattle is higher in the presence of additives that modulate ruminal fermentation, which increases propionate production, the primary glucose precursor in the liver (Duffield, Merrill & Bagg, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…However, when fed a high-concentrate diet, values can exceed 70 mg dL −1 . For example, Aferri et al (2019) found 129.23 mg dL −1 of blood glucose in Nellore cattle confined with 800 g kg DM −1 of concentrate in the diet. Furthermore, glycemia in cattle is higher in the presence of additives that modulate ruminal fermentation, which increases propionate production, the primary glucose precursor in the liver (Duffield, Merrill & Bagg, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…O pós-parto de primíparas pode ser bastante desafiador, uma vez que, além das exigências de mantença, gestação e lactação, necessitam de nutrientes para seu próprio crescimento; assim, não atendidas estas exigências, podem não demonstrar cio fértil durante a lactação (NOGUEIRA et al, 2014) Diversos estudos avaliaram os efeitos da nutrição e metabolismo pós-parto em vacas leiteiras de diferentes ordens de parto (NASROLLAHI et al, 2017;NEAVE et al, 2017;TIENKEN et al, 2015;SAQIB et al, 2018), no entanto, a respeito de vacas de corte em condição de pastejo, ainda são escassos os trabalhos que avaliaram os efeitos da suplementação no pós-parto no metabolismo de diferentes ordens de parto.…”
Section: Introductionunclassified